1997
DOI: 10.1074/jbc.272.2.1395
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of Shear Stress on Extracellular Signal-regulated Kinase and N-terminal Jun Kinase in Endothelial Cells

Abstract: Shear stress differentially regulates production of many vasoactive factors at the level of gene expression in endothelial cells that may be mediated by mitogenactivated protein kinases, including extracellular signal-regulated kinase (ERK) and N-terminal Jun kinase (JNK). Here we show, using bovine aortic endothelial cells (BAEC), that shear stress differentially regulates ERK and JNK by mechanisms involving G i2 and pertussis toxin (PTx)-insensitive G-protein-dependent pathways, respectively. Shear activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
264
4
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 251 publications
(292 citation statements)
references
References 57 publications
23
264
4
1
Order By: Relevance
“…Bovine aortic endothelial cells (BAEC) harvested from descending thoracic aortas were maintained (37°C, 5% CO 2) in a growth medium [Dulbecco's modified Eagle's medium (DMEM) containing 1 g/l glucose (GIBCO) and 20% fetal bovine serum (FBS, Atlanta Biologicals) without antibiotics] (26). BAEC used in this study were between passages 5 and 10.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bovine aortic endothelial cells (BAEC) harvested from descending thoracic aortas were maintained (37°C, 5% CO 2) in a growth medium [Dulbecco's modified Eagle's medium (DMEM) containing 1 g/l glucose (GIBCO) and 20% fetal bovine serum (FBS, Atlanta Biologicals) without antibiotics] (26). BAEC used in this study were between passages 5 and 10.…”
Section: Methodsmentioning
confidence: 99%
“…Aliquots of cell lysates (20 g protein each) were resolved on a 10% SDS-PAGE gel and transferred to a polyvinylidene difluoride membrane (Millipore) (26). The membrane was incubated with a primary antibody overnight at 4°C and then with a secondary antibody conjugated with alkaline phosphatases (1 h at room temperature), which were detected by a chemiluminescence method (26).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animals were designated as "in labor" when at least one pup was delivered. After mating, myometrial samples were collected on days 15,17,19,21,22,23, or 1 day postpartum (1PP; n ϭ 3). At the time of tissue collection, the ligated empty horn was separated from the gravid horn.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment of endothelial cells with anti-sense G q oligonucleotides inhibits shear stress-induced Ras-GTPase activity, while the transfection of G 1 2 enhances the shear stress-induced Ras activation [78]. It has also been reported that the shear stress-mediated activation of ERK1/2 is abolished by the treatment of endothelial cells with the G i inhibitor pertussis toxin [79]. In addition, shear stress increases the activity of G proteins reconstituted in liposomes in the absence of protein receptors [80].…”
Section: G-protein-coupled Receptors (Gpcrs) and G Proteinsmentioning
confidence: 94%